STATE PROGRAM OF THE REPUBLIC OF NORTH OSSETIA-ALANIA «PROMOTION OF EMPLOYMENT OF THE REPUBLIC OF NORTH OSSETIA-ALANIA» 2014-2018 AND ITS IMPACT ON DEMOGRAPHIC PROCESSES IN THE REPUBLIC - Z. Pashaeva (Вестник университета)
The article describes the features of influence of the state program of the Republic of North Ossetia-Alania «Promoting the employment of the population of North Ossetia-Alania» on 2014-2018 on the demographic processes in the region. Made by the author conclusions are compared with the findings of similar programs in other regions of Russia. Expected results of the program are considered in conjunction with the expected forecast in demographic development of the country.